Living wishes : a communication campaign encouraging Singapore residents aged 35 to 59 to initiate Advance Care Planning discussions with their elderly parents - Chong, Charlotte Wen Wei (Nanyang Technological University, 2022)
This paper presents Living Wishes, a communication campaign aimed at increasing Advance Care Planning (ACP) discussions between adults and their elderly parents so that they are better prepared to handle their elderly parents’ end-of-life (EOL) care. The culture of silence surrounding ACP in Singapore has led to low awareness, knowledge and take-up rates for ACP. This brings about significant issues, such as the loss of patient autonomy and increased burden on one’s family members when it comes to making important decisions about one’s EOL care. Using insights garnered from formative research, the campaign aimed to encourage ACP conversations between adults and their elderly parents by provoking reflection on the former’s relationship with their parents and their mortality. The campaign was split into two main phases: it first focused on raising awareness and understanding of ACP among the TA. In the second phase, the TA was encouraged to engage in ACP conversations with their elderly parents. Campaign tactics include digital, on-the-ground and media outreach efforts, including a Christmas reflection event to spark awareness about ACP, a free postcard mailing event and a Conversation Starter Kit for adults to kickstart ACP conversations with their parents. As a result of our campaign, 15.7% of our post-campaign experimental group became aware of ACP while 17.5% of them completed ACP discussions with their parents. This paper will cover the campaign’s research, development, execution, evaluation, limitations and future recommendations. A full list of documents and research data can be found in the appendices.